Production and characterization of polyclonal antibodies against Xanthomonas campestris pv. viticola - Araujo, João Sebastião de Paula; Cruz, Fábio Bueno dos Reis; Cruz, Geraldo Baeta; Oliveira, Bruno Cardoso de; Robbs, Charles Frederick; Ribeiro, Raul de Lucena Duarte; Polidoro, José Carlos (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to produce polyclonal antibodies against Xanthomonas campestris pv. viticola and characterize these antibodies through Elisa serological indirect method. Results indicate that polyclonal antibodies produced were highly reactive against bacterial cells, showing specificity at the pathovar level and potential to be used for diagnosis and certification purposes.